2013
DOI: 10.4062/biomolther.2013.055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Codonopsis lanceolata with Steamed and Fermented Process on Scopolamine-Induced Memory Impairment in Mice

Abstract: Codonopsis lanceolata (Campanulaceae) traditionally have been used as a tonic and to treat patients with lung abscesses. Recently, it was proposed that the extract and some compounds isolated from C. lanceolata reversed scopolamine-induced memory and learning deficits. The purpose of this study was to evaluate the improvement of cognitive enhancing effect of C. lanceolata by steam and fermentation process in scopolamine-induced memory impairment mice models by passive avoidance test and Morris water maze test.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…Recently, we verified that the fermented C. lanceolata ameliorated memory and learning impairment and the steamed and fermentation process significantly improved the cognitive recognition activity compared to original C. lanceolata [1820]. In the present study, we modified the steamed and fermentation process for mass production of fermented C. lanceolata and confirmed the effect of fermented C. lanceolata on memory and learning impairment using scopolamine-induced memory deficits in the Morris water maze and passive avoidance tests.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Recently, we verified that the fermented C. lanceolata ameliorated memory and learning impairment and the steamed and fermentation process significantly improved the cognitive recognition activity compared to original C. lanceolata [1820]. In the present study, we modified the steamed and fermentation process for mass production of fermented C. lanceolata and confirmed the effect of fermented C. lanceolata on memory and learning impairment using scopolamine-induced memory deficits in the Morris water maze and passive avoidance tests.…”
Section: Introductionsupporting
confidence: 72%
“…The water maze test was performed as described in our previous study [18, 21]. The water maze consisted of a circular pool (90 cm diameter and 40 cm height) filled with water up to 30 cm and maintained at 20 ± 1°C and areas of the maze were defined as four equal quadrants.…”
Section: Methodsmentioning
confidence: 99%
“…Morris water maze test was carried out as method previously described [9, 13]. The water maze was consisted of large circle pool and was filled to a depth of 30 cm with opaque water with white milk.…”
Section: Methodsmentioning
confidence: 99%
“…Passive avoidance test was performed according to previously described method [13, 14]. Passive avoidance apparatus consists of light compartments and dark compartments with an electrifiable grid floor.…”
Section: Methodsmentioning
confidence: 99%
“…These saponins are used in the treatment of high blood pressure and in lung infl ammation such as asthma, tonsillitis and pharyngitis. A previous report has indicated that C. lanceolata show antilipogenic and anti-infl ammatory effects in mice with alcohol-induced fatty liver and also help in the treatment of cancer disease due to having polyacetylenes, phenylpropanoids, alkaloids, triterpenoids and polysaccharides, which contribute to multiple bioactivities (Weon et al 2013 ;He et al 2015 ) .…”
Section: Codonopsis Lanceolata (Siebold and Zucc) Trautvmentioning
confidence: 99%